PENGARUH REAL EARNING MANAGEMENT TERHADAP LABA OPERASIONAL DAN ARUS KAS AKTIVITAS OPERASIONAL PERUSAHAAN DI MASA MENDATANG DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Periode Penelitian Tahun 2013 s.d 2016) - Desti Monika Uli; Amries Rusli Tanjung; Azwir Nasir (PEKBIS, 2019)
This study aims to analyze influence of real earning management towardsoperational profit and cash flow of the company's operational activities in the futurewith audit quality as moderating variable in the manufacture company listed inIndonesia Stock Exchange research period 2013-2016. The population in this studyare Manufacturing companies listed on the Indonesia Stock Exchange Period 2031-2016. The sampling technique used purposive sampling method which resulted in asample of 43 Manufacturing companies. Researchers used multiple linearregression techniques and moderated regression analysis (MRA). The resultsshowed that 1). real earning management has impact toward operational profit; 2).real earning management has impacted toward the company's operational cash flowactivities in the future; 3). audit quality moderates the effect of real earningmanagement toward operational profit; 4). audit quality does not moderate the effectof real earning management toward cash flow of the company's operational activitiesin the future.